Mitochondrial dysfunction and altered ribostasis in hippocampal neurons with cytoplasmic inclusions of multiple system atrophy. Issue 4 (1st July 2018) - Maeda, Norihisa; Honda, Hiroyuki; Suzuki, Satoshi O.; Fujii, Naoki; Kira, Jun‐ichi; Iwaki, Toru
Abstract : Multiple system atrophy (MSA) is a sporadic adult‐onset neurodegenerative disease. It has recently been shown that patients with MSA accompanied by cognitive decline display numerous neuronal cytoplasmic inclusions (NCIs) in the limbic neurons. We examined potential mechanisms underlying the formation of these NCIs by determining of mitochondrial function and statuses of RNA processing by analyzing 12 pathologically confirmed cases of MSA. Among them, four had cognitive impairment Semiquantitative evaluation using immunohistochemistry analyses revealed a significantly greater NCI burden in the hippocampal cornu ammonis 1 (CA1) subfield, subiculum, and amygdala in the cases with cognitive impairments compared with those without cognitive impairment. Immunofluorescent staining revealed that limbic neurons with NCIs often accelerated production of reactive oxygen species (ROS) and degraded mitochondrial quality control. Immunofluorescent staining also revealed that neurons with these NCIs translocated heterogeneous nuclear ribonucleoprotein A1 (HNRNPA1) from the nucleus and aggregated abnormally at the perinuclear rim. Since the NCIs in the hippocampal neurons of MSA with cognitive impairments were more numerous, the neuronal mitochondrial dysfunction and altered ribostasis observed in NCI formation may be involved in the hippocampal degeneration of MSA.